Ignitability and Explosibility of Gases and Vapors - Ma, Tingguang; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2015)
The book provides a systematic view on flammability and a collection of solved engineering problems in the fields of dilution and purge, mine gas safety, clean burning safety and gas suppression modeling. For the first time, fundamental principles of energy conservation are used to develop theoretical flammability diagrams and are then explored to understand various safety-related mixing problems. This provides the basis for a fully-analytical solution to any flammability problem. Instead of the traditional view that flammability is a fundamental material property, here flammability is discovered to be a result of the explosibility of air and the ignitability of fuel, or a process property. By exploring the more fundamental concepts of explosibility and ignitability, the safety targets of dilution and purge can be better defined and utilized for guiding safe operations in process safety. This book provides various engineering approaches to mixture flammability, benefiting not only the safety students, but also field operators, as a useful resource for the safe handling of flammable gases and liquids. It will be useful to anyone who worries about the ignition potential of a flammable mixture.  .
A historical review -- Classical flammability theories -- Combustion fundamentals -- Thermal balance methods -- Ignitability, flammability and explosibility -- Operations within Flammability Diagrams -- Applications on Fuel Streams (Type II problems) -- Applications in Compartment Fires (Type I problem) -- Summary and conclusions.
Keywords: Chemical engineering; Chemistry; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Industrial Chemistry/Chemical Engineering; Safety in Chemistry, Dangerous Goods; Engineering Thermodynamics, Heat and Mass Transfer; Thermodynamics